Identidad cultural en los contenidos digitales en Positiva TV de Riobamba: representación y audiencia, periodo noviembre 2023 - junio 2024 - Mosquera Chichande, Emily Ninoska (2025)
This research focuses on analyzing how cultural identity is represented in the digital content disseminated by Radio Positiva TV, as well as its impact on young people aged 18 to 30 in the city of Riobamba, from November 2023 to June 2024. The methodology employed is a mixed-method approach, applying both qualitative and quantitative content analysis matrices to posts made on Facebook among young people in Riobamba. Those surveys, consisting of 14 questions, were also conducted. Additionally, unstructured interviews were conducted with an expert in cultural identity and the media outlet, which provided professional and impartial assessments of the problem at hand. The results reveal low cultural consumption among the young audience, although specific segments such as "La Riobambeñidad" and the "Diablo de Lata" contest managed to generate positive emotional responses. Limited audience participation and a partial representation of local cultural diversity were also identified. Given these findings, there is a need to strengthen cultural content with a more inclusive, critical, and participatory approach. To this end, a journalistic style manual was developed to serve as a tool to improve the representation of cultural identity in digital media.